Pericytes: The lung-forgotten cell type - Garrison, Annelise T.; Bignold, Rebecca E.; Wu, Xinhui; Johnson, Jill R. (Frontiers in Physiology, 2023)
Pericytes are a heterogeneous population of mesenchymal cells located on the abluminal surface of microvessels, where they provide structural and biochemical support. Pericytes have been implicated in numerous lung diseases due including pulmonary arterial hypertension (PAH) and allergic asthma due to their ability to differentiate into scar-forming myofibroblasts, leading to collagen deposition and matrix remodelling and thus driving tissue fibrosis. Pericyte-extracellular matrix interactions as well as other biochemical cues play crucial roles in these processes. As an important functional component of the pulmonary vasculature, pericytes are involved in a number of chronic lung diseases. In this review, we give an overview of lung pericytes, the key pro-fibrotic mediators they interact with, and detail recent advances in preclinical studies on how pericytes are disrupted and contribute to lung diseases including pulmonary arterial hypertension (PAH), allergic asthma, and chronic obstructive pulmonary disease (COPD).Several recent studies using mouse models of PAH have demonstrated that pericytes contribute to these pathological events; efforts are currently underway to mitigate pericyte dysfunction in PAH by targeting the TGF-β, CXCR7, and CXCR4 signalling pathways. In allergic asthma, the dissociation of pericytes from the endothelium of blood vessels and their migration towards inflamed areas of the airway contribute to the characteristic airway remodelling observed in allergic asthma. Although several factors have been suggested to influence this migration such as TGF-β, IL-4, IL-13, and periostin, recent evidence points to the CXCL12/CXCR4 pathway as a potential therapeutic target. Pericytes might also play an essential role in lung dysfunction in response to ageing, as they are responsive to environmental risk factors such as cigarette smoke and air pollutants, which are the main drivers of COPD. However, there is currently no direct evidence delineating the contribution of pericytes to COPD pathology. Although there is a lack of human clinical data, the recent available evidence derived from in vitro and animal-based models shows that pericytes play important roles in the initiation and maintenance of chronic lung diseases and are amenable to pharmacological interventions. Therefore, further studies in this field are required to elucidate if targeting pericytes can treat lung diseases.